ANALISIS YURIDIS LEGALISASI TINDAKAN ABORSI BERDASARKAN UU NO. 36 TAHUN 2009 TENTANG KESEHATAN - Silvia Kusumaningrum (2021)
Abortion is the termination of a pregnancy by the removal of the fetus or embryo before it has the ability to survive outside the womb, resulting in death. In the perspective of positive law in Indonesia, the act of abortion in certain cases is an act that can be justified or legal based on certain medical indications which are regulated in Article 75 paragraph (2) of Law no. 36 of 2009 concerning Health. The issue raised is a juridical analysis related to the legalization of abortion based on Law no. 36 of 2009 concerning health and how the procedure for abortion acts is legalized according to applicable law in Indonesia. This type of research is juridical normative with technical descriptive qualitative data analysis methods in studying data using literature study methods.